Influencias morfogenéticas de los desalineamientos y lineas de costa contrapuestas en el litoral de Chile central - Araya Vergara, José F. (Investigaciones Geográficas: Una mirada desde el sur, 1983)
Two morphostructural styles are present in the coastline Topocalrna - Pichilernu (34° - 34°30’ S): a) Offset style with zeta bays and b) Offset style with crenulate coastlines and almost straight beaches. They are resulting from contraposed shorelines, as evidenced by overlapping softer desposits on crystalline hard rocks. Systern atributes are recognized in these styles by using components as offset angle, asymetry, orientation and curvature index. Correlation and matrices analysis indicate that 40 - 60% of the effects are explained by three components: offset angle, curvature index and azirmuth. Therefore, both of the styles may be recognized as subsystems. Each subsystem presents a different behaviour in front of wave environment Since offset condition and orientation explain curvature, each style receives differential wave attack, because refraction is well and positively correlated to curvature. Half heart shaped beaches and bays represent, therefore, both drift and swash alignment, depending on the offset angle and refraction of constructing waves. So, a logarithmic spiral may appear. Their maximum concavity is eroded during surges, meanwhile the downdrift part’can suffer depositional effect. This difference is not so clear in the almost rectilinear beaches of the other style. State and attack conditions depend, therefore, on the position in the bay. Dune system structures associated to beaches may be correlated to sedimentary budget and beach orientation. This fact must be taken into account in decision making processes concerning shore managernent.